The Impact of COVID-19 on Formal Firms : Evidence from Albania - Bachas, Pierre (World Bank, Washington, DC, 2020)
The COVID19 (coronavirus) pandemic and associated containment measures are expected to cause far-reaching damage to economies around the world. Firms are suffering from reduced demand due to movement restrictions, from reduced labor supply and from constraints to sourcing material inputs. The breakup of otherwise healthy businesses in response to a temporary shock implies large social costs. Governments are therefore intent on designing emergency policies to keep businesses afloat. The authors present simulations using firm-level tax records from Albania, which vary the duration of the lockdown and the relative impact across sectors.